De la gran transformación a la gran financiarización. Sobre Karl Polanyi y otros ensayos - Quiroz, Omar (Foro Internacional, 2019)
Political Science
Keywords: From the Great Transformation to the Great Financialization (Book); book review

¿Cooptación o resistencia? Problematizando las estrategias legales y derechos de los movimientos sociales en el dominio socio-económico - Fierro, Alberto (Co-optation or resistance? Problematizing legal strategies and rights for social movements in the socio-economic domain., 2018)
This paper elaborates an analytical template to problematize the politics of legal strategies and rights. In the literature, scholars have been arguing that courts have an individualizing effect on collective struggles, or that (human) rights constitute neoliberal subjects. Yet, it is possible to open this theoretical understanding to further complexities: the inclusion of movements into certain governmentalities may have positive effects for their struggle. The discussion follows two main argumentative axes: first, social movements using legal tools and rights language are possibly deploying strategies of 'counter-conducts': exactly because the law is part and parcel of neoliberal governmentalities, it can constitute a strategic element to redirect and subvert established power relationships. Second, rights in the socio-economic domain (e.g. labor, housing and land) have specific properties which work against economic neoliberalism. Following a classic Polanyian argument, the idea of socioeconomic rights pulls away these goods from the market domain. This creates difficulties to the capitalist economic system, which is based on a rather strict conception of land and housing as commodities. (English)
Political Science; International Relations
Keywords: Derechos; contraconductas; counterconducts; estrategias legales; governmentality; gubernamentalidad; legal strategies; movimientos sociales; rights; social movements

Karl Polanyi. El Racionalismo Económico Como Motor De La Utopía Liberal - Goikoetxea Berdonces, Maialen (KARL POLANYI. THE ECONOMIC RATIONALISM AS THE MOTOR OF THE LIBERAL UTOPIA., 2018)
Karl Polanyi's main thesis is the effective separation of society and economy, placing the economy above the society. This artificial separation will be carried out by a series of theoretical tools and mechanisms -the introduction of fictitious goods and economic rationalism as a social premise- that will blind an overall view of the social panorama, focusing only on the economic aspects of it, causing that way, an unprecedented human crisis. (English)
Political Science; Philosophy
Keywords: capitalism; capitalismo; economic rationalism; fictitious goods; liberal utopia; mercancías ficticias; racionalismo económico; utopía liberal

La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
History; Anthropology; Economics
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences

Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Philosophy; Economics
Keywords: MISES; Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica

Aristóteles Descubre La Economía, Para Temerla. Una Lectura Desde Karl Polanyi - Polo Blanco, Jorge (ARISTOTLE DISCOVERS ECONOMY, TO FEAR IT. A READING THROUGH THE EYES OF KARL POLANYI., 2017)
This study approaches Aristotelian reflections on economy through the eyes of Karl Polanyi, as he resorts to the Greek philosopher to find useful elements when building a profound criticism of the modern market society. Aristotle intuited the uncertain future of a social order devoured by economic relations expanding at a hypertrophic rate. In his time, indeed, this was only a potential threat —he never saw the effective culmination of anything like what we are seeing today—. But he was nevertheless able to see the ultimate meaning of what was at stake, and to understand that the unmeasured, uncontrolled growth of market relations would irremediably affect civic balance. He understood that the unrestricted extension of the desire for profit to all human ties would be a powerful threat to the heart of the political community. (English)
Economics
Keywords: Aristotelian economic philosophy; ECONOMÍA DE LA ANTIGUA POLIS; FILOSOFÍA ECONÓMICA ARISTOTÉLICA; ancient capitalism; capitalismo antiguo; economic of ancient polis; market society; sociedad de mercado

¿Incrustamiento sin espacio? Situando el comercio justo en la industria florícola ecuatoriana - Lyall, Angus (Embeddedness without a space? Situating fair trade in the Ecuadorian flower industry., 2015)
In the last two decades, Fairtrade International has consolidated as the largest fair trade certifier in the world. Much of its growth has involved the expansion of its practices from exclusively certifying cooperatives of smallholder farmers to regulating agroindustries and nonagricultural companies. In hired labor contexts, Fairtrade claims to improve labor and environmental conditions and promote local development and many researchers praise Fairtrade for "re-embedding" economic relations in social and ethnical ones. In this article, I highlight the testimonies of workers on three certified Ecuadorian flower plantations, who acknowledge many of these claims, but remind us that framing Fairtrade as a mechanism for "re-embedding" economic relations elides the desire among workers to leave the flower industry and re-embed their economic relations in local social space. Whereas Polanyi conceives of embeddedness in historically and geographically situated relations, I argue that academic approaches to Fairtrade often misappropriate his notion of the concept by employing it to describe abstract relations between consumers and workers. I place this concept in dialogue with the work of Henri Lefebvre on social space and territory to re-conceptualize what an embedded territorial development might look like under Fairtrade and to foreground the limits and contradictions of this mechanism. (English)
Political Science
Keywords: Ecuador; LEFEBVRE; Henri; comercio justo; embeddedness; espacio social; fair trade; flower industry; incrustamiento; industria florícola; social economy; social space

Acerca del renovado interés por Karl Polanyi - Subirats, Joan (Sobre o interesse renovado de Karl Polanyi., 2014)
¿Cómo es posible que un libro escrito hace setenta años despierte hoy un renovado interés y que sirva para hacer mejores diagnósticos sobre la crisis económica y sus posibles alternativas? En este texto trataremos de dar respuesta a este interrogante, mostrando los elementos que hacen de la obra de Polanyi un buen punto de partida para observar la crisis de legitimidad política y los problemas de relación entre economía de mercado y sistema político. La crítica de Polanyi a la naturalización de la economía de mercado es hoy plenamente actual. (Spanish)
Political Science
Keywords: bens comuns; bienes comunes; capitalismo; crises econômica; crisis económica; economia de mercado; economía de mercado; relaciones estado y sociedad; relações de estado e sociedade

Género y cuidados: respuestas sociales e institucionales al surgimiento de la sociedad de mercado en el contexto europeo - Carbonell Esteller, Montserrat; Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (GENDER AND CARE: SOCIAL AND INSTITUTIONAL ANSWERS TO THE DEVELOPMENT OF THE MARKET ECONOMY IN EUROPE., 2014)
This article examines from a care approach the social and institutional responses to the development of the market economy in the European context. Studying this long period -which Polanyi called the double movement- is relevant because it constitutes the historical process by which the interests of the market, the logic of profits and its social and scientific naturalization come to dominate. Since then, the importance of care work in people's life, the reproduction of the labour force, and the provision of welfare and social insurance have been ignored. Until very recently, historical analyses have focused on the emergence of the Welfare State, regardless of how the state's answers interacted or modeled with other spheres of welfare provision, especially the family through women's unpaid work. The article focuses on the European experience and the period analyzed comprehends the disintegration of communal and assistance care with the Old Regime Crisis, the development of charity and associations as solutions to the inhibition of the Liberal State in the 19th century -solutions that were limited and insufficient, leading to the state assumption of the care and assistance functions, embryo of the development of later Welfare States after World War II. (English)
Economics
Keywords: capitalismo liberal; care; cuidados; estados del bienestar; gender; género; liberal capitalism; modelos asistenciales pre-industriales; pre-industrial mutual aid regimes; welfare state

Actualidad de la crítica de Karl Polanyi a la sociedad de mercados - Maya Ambía, Carlos Javier (Política y Cultura, 2014)
Karl Polanyi's critique of market society is a very powerful tool for understanding our current social reality. It helps us to formulate a creative and purposeful proposal that contributes to build a just, equitable, and more humane society, that would be committed to the future life on the planet. A comparison between the society criticized by Polanyi and ours, leads us to discover the validity of his basic concepts and his method for the preparation of a new critical discourse that not only takes advantage of the legacy of the author, but also expands, clarifies and updates it. (English)
Sociology
Keywords: crítica social; doble movimiento; double movement; market society; mercado autorregulado; self-regulated market; social critique; sociedad de mercado

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Economics; Development Studies
Keywords: Great Transformation; The (Book); primitive societies

Crisis del modelo neoliberal, hacia una planificación regional. Un aporte polanyiano - Valderrama Saud, Paula (Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution., 2014)
Using Karl Polanyi's analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called "mass democracy." Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the beginning of a new era characterized by greater regional planning and a plurality of development paths. (English)
Economics
Keywords: European Union; Latin America; crisis; democracia; democracy; globalization; government policy; market; mercado; neoliberalism; neoliberalismo; planificación regional; regional planning

El Debate Moderno Sobre Los Escritos Económicos Aristotélicos - Borisonik, Hernán (The modern debate on the Aristotelian economic writings., 2013)
The present article is a critical reading of the most important modern interpretations on Aristotle's economic writings. Firstly, the debate between the “primitivists" and the “modernists" (headed by Rodbertus, Bücher and Meyer) will be studied. Then, the readings of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley, will be analyzed, considering these authors as the most renowned commentators of the Aristotelian economical legacy. (English)
Political Science
Keywords: ARISTOTLE; Aristóteles; FINLEY; M. I. (Moses Israel); 1912-1986; MARX; Karl; 1818-1883; SCHUMPETER; Joseph Alois; 1883-1950; economic research; economics; economía; history of economics; primitivism and modernism; primitivismo y modernismo

Los aborígenes colombianos y las paradojas del desarrollo: el caso de los emberá katíos del Alto Sinú - Martínez Triviño, Ana Milena; Reyes Albarracín, Fredy Leonardo (Colombian indigenous and the paradoxes of development: the case of the emberá katios from High Sinú., 2013)
In 1992 the construction of the Urra I hydroelectric begins, one of the most ambitious energy projects in the recent history of Colombia. Located in the inhospitable jungle region of High Sinú -northwest of the Andean territory- the environmental license granted by government entities ignored the ecological and environmental impacts the work would entail, and also failed to recognize the presence of the emberákatio indigenous people, whose constitutional rights were violated. Following the arguments presented by the economist Karl Polanyi, the article explores the environmental, social and cultural consequences caused by the energy project, in addition to delving in the strategy of violence and extermination that paramilitarism created to disrupt the organizational processes for the emberákatios, which resulted in the disappearance and murder of indigenous leaders. (English)
Political Science; International Relations
Keywords: aborígenes; fictitiuos merchanidise; indigenous; mercado autorregulado; mercancías ficticias; paramilitarism; paramilitarismo; self-regulated market; violence; violencia

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Economics
Keywords: economic determinism; economic totalization; economicism

Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Geography
Keywords: 21st century; POLANYI; Karl; 1886-1964; crisis; economic history; global financial crisis; 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio – Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Economics
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica

Contrastes entre las reformas laborales del Japón y la República de Corea - Yun, Ji-Whan (Revista Internacional del Trabajo, 2011)
El Japón y la República de Corea acometieron a finales de los años noventa una serie de reformas del mercado de trabajo que se han presentado muchas veces como meramente flexibilizadoras. Sin embargo, el autor sostiene —sobre la base del concepto de «doble movimiento» de Polanyi— que los dos conjugaron las medidas liberalizadoras con otras en pos de la estabilidad social. Tras estudiar las leyes adoptadas por uno y otro para reformar su mercado de trabajo y atenuar la dualidad del mismo, afirma que las diferencias se deben a que tienen procedimientos y entornos distintos para fijar sus líneas políticas.
Political Science
Keywords: Corea; Japan; Japón; República de; comentario; flexibilidad del trabajo; política laboral; protección social; segmentación del mercado de trabajo; seguridad del empleo

Una lectura transversal de la Formación Profesional Ocupacional pública: entre Karl Polanyi, Max Weber y Michel Foucault - Dautrey, Philippe (Cuadernos de Trabajo Social (Espana) Vol. 22, 2009)
La formación profesional ocupacional (FPO) se ubica en una encrucijada de problemáticas que analizaron tanto Karl Polanyi como Max Weber y Michel Foucault. Por un lado, el papel fundamental que desempeñan los mercados autorregulados en el nuevo gran cambio que significa la globalización suscita un movimiento contraprotector del que participa esta capacitación para el empleo. Por otro, respalda el desarrollo de la organización racional capitalista, la cual a su vez implica su racionalización. Por último, es parte del control social que tal organización necesita para llevar a cabo sus propósitos. En resumen, las todavía relevantes obras de dichos estudiosos ofrecen una perspectiva diacrónica sobre el entorno de la FPO. También permiten apreciar el papel equívoco que ésta cumple respecto al desenvolvimiento y a los valores del sistema socio-económico vigente. ENG: The occupational vocational training (FPO) is located at a crossroads of problems that analyzed both Karl Polanyisuch as Max Weber and Michel Foucault. On the one hand, the fundamental role played by self-regulated markets in the new great change that globalization means provokes a counterprotective movement in which this training for employment is involved. On the other, it supports the development of rational capitalist organization, which in turn implies its rationalization. Finally, it is part of the social control that such organization needs to carry out its purposes. In summary, the still relevant works of these scholars offer a diachronic perspective on the environment of the FPO. They also allow us to appreciate the equivocal role it plays in respect to the development and values ​​of the current socio-economic system.
Sociology
Keywords: FOUCAULT; Michel; 1926-1984; Post-Fordism; Spain; WEBER; Max; 1864-1920; capitalism; capitalismo; control social; employment; formacion profesional; knowledge economy; racionalizacion de la economia; rationalization of the economy; social control; vocational training; work

Karl Polanyi y el Problema De Los Mercados - Colombo, Octavio (Studia historica., 2008)
The purpose of this work is to analyze the Karl Polanyi’s conceptions about the pre-capitalist-markets, especially his revision of the categories of trade, money and market. In first place, we present a critical examination of the fundamental ideas of The Great Transformation, where his later reflections about pre-industrial societies are ground. Using some basic categories of the critique of political economy, we treat to show certain methodological and conceptual limits of his proposal. Then, we analyze the Polanyi’s ideas related to the features of pre-capitalist markets. We conclude that, even when the polanyian categories and reasoning need a deep revision, his merit is to propose a really historical approach about the markets; approach that until now has not received a suitable attention.
History
Keywords: Great Transformation; The (Book); critique; great transformation; pre-capitalist markets; preindustrial society

Karl Polanyi o la humildad de las ciencias sociales - Rendueles, César (NEXO. Revista de Filosofía, 2004)
EN: This essay proposes a periodization of Karl Polanyi’s work, from his early writings in Vienna to his anthropological work developed in the context of the substantivist-formalist discussion. The outstanding feature of this studies is the way they combine empirical sharpness with epistemological modesty. Unlike orthodox economy and imperialism theories, Polanyi doesn’t ignore the precarious theoretical situation of social science. His investigations are based on empirical thesis both broadly accepted and heuristically productive. Este artículo analiza las distintas fases de la obra de Karl Polanyi, desde sus pri- meros escritos en Viena a su obra antropológica en el contexto del debate entre sus- tativistas y formalistas. La principal virtud de estos estudios es su mezcla de acier- to empírico y modestia epistemológica. A diferencia de la economía ortodoxa o de las teorías del imperialismo, Polanyi no rehuye la precaria situación teórica de las ciencias sociales. Sus investigaciones se basan en tesis empíricas ampliamente aceptadas que, sin embargo, demuestran una notable vitalidad heurística.
Sociology
Keywords: Karl Polanyi; epistemology; periodization; social science

¿Uno de los nuestros?: otra vuelta de tuerca al marxismo de Karl Polanyi - Rodríguez, Sergio Braulio Véliz (El Buho: Revista electrónica de la Asociación Andaluza de Filosofía, 2022)
Este ensayo trata de situar la obra de Karl Polanyi en la tradición del pensamiento marxista heterodoxo, respondiendo a las objeciones que se han planteado en contra de tal filiación. Se analizan para ello los conceptos fundamentales del pensamiento del autor desde un punto de vista marxista: la “economía sustantiva” y la “economía formal”, la “falacia economicista”, la “incrustación” (Embeddedness) de la economía, las “mercancías ficticias” y el “doble movimiento”.
Philosophy
Keywords: Marxism; double movement; economi; economistic fallacy; embeddedness; embeddness; fictitious commodities; formal economy; substantive economy

Discussions around Argentine Capitalism: Economic Debate and Contribution of Karl Polanyi for Our Days - Rossi, Ignacio Andrés (2022)
The article proposes to address the current discussions about national capitalism and the Argentine economy from a set of canonical ideas of the work of Karl Polanyi. Argentina, which for several decades has been going through recurring crises in its economic model, awakens a plurality of voices from social scientists and specialized journalists who debate the problems, limitations and projections of national capitalism. For this, we have surveyed these discussions, to a greater extent, from the specialized press and the recently published bibliography, paying attention to the theoretical, interpretative and ideological proposals that allow us to generate relationships with Polanyi's theory. It was concluded that the latter's ideas about the functioning of capitalism, markets, the State and contemporary social dynamics provide significant conceptual background to frame the current discussions among social scientists about the Argentine economy.
Economics
Keywords: Argentina; capitalism; development; stability; state

Requisitos para el cambio transformativo: contribuciones de Karl Polanyi - Kirby, Peadar (International Review of Economic Policy-Revista Internacional de Política Económica, 2020)
Una pregunta clave que surge de la pandemia de coronavirus es qué se requiere para hacer de esta fase temporal un camino hacia el cambio transformador. O, como sucedió en gran medida después de la crisis financiera de 2008, ¿volverá la sociedad a una economía dominada por el crecimiento y cargada de carbono basada en una ética del individualismo radical y el consumismo desenfrenado, informada por recetas neoliberales? Este artículo se basa en el trabajo de Karl Polanyi (1886-1964) para ofrecer un marco teórico alternativo para guiar el cambio social transformador en la era del cambio climático. Comienza por identificar una característica clave del equilibrio entre la estructura y la agencia en la sociedad contemporánea, a saber, un optimismo tecnológico y propone un marco alternativo a través de la economía política. La segunda sección identifica los dos marcos teóricos clave que informaron las configuraciones dominantes de la economía política desde la Segunda Guerra Mundial: un marco socialdemócrata y un marco neoliberal. Se argumenta que ahora es necesario un nuevo marco. La tercera y más larga sección dibuja una gama de contribuciones conceptuales de Polanyi para ofrecer una teoría distintivamente diferente a la que ofrece el neoliberalismo. Estos incluyen: sociedad de mercado; diferentes significados de economía; mercancías ficticias; formas de integración; doble movimiento; descubrimiento de la sociedad; la persona humana y la libertad; y el poder de la tecnología. La sección final saca conclusiones.
Economics
Keywords: COVID-19; climate change; market society; neoliberalism

Economía de mercado, globalización y migración: retos y rostros de las personas vulneradas globales. Un análisis desde Karl Polanyi - Franco, Jefferson Frenel Junior Pierrelus (Contextualizaciones Latinoamericanas, 2020)
Este ensayo pretende demostrar cómo el mercado autorregulado que pregonael neoliberalismo es una falacia y que tiende tarde que temprano a acabar odestruir las propias condiciones sociales, ambientales y culturales que aseguranla vida en el planeta. Basado en una globalización financierista, en la privatización yen la liberalización de mercado, ese modelo se ha convertido en la mayor fábrica deempobrecidos, logrando cooptar y subordinar a los Estados a sus designios a travésde las grandes empresas transnacionales e instituciones económicas internacionales.La neo-esclavitud, la miseria, la precariedad y la violencia se han instalado como unmodo de ser y de vivir, aunadas a la emigración, debido a esa explotación, extracciónde recursos naturales a ultranza que lleva a cabo ese modelo económico imperante.Hay voces, manifestaciones, como la de Karl Polanyi, que quieren poner un freno a esemolino satánico, llamado neoliberalismo.
Economics; Political Science
Keywords: economía de mercado; globalización; globalization; market economy; migración; violence; violencia